Comparison of complications following primary and secondary wound closure after surgical extraction of impacted mandibular third molars among patients visiting a tertiary care center, Gandaki Province - Poudel, Dhruba Chandra; Koirala, Ujjwal (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: The surgical extraction of impacted mandibular third molars is often associated with post-operative complications and is affected by degree of impaction, surgical technique, operator skill and wound closure method. The purpose of this study was to compare the effect of primary and secondary wound closure after surgical removal of impacted mandibular third molars.Methods: A hospital-based cross-sectional study was conducted in 40 patients and were divided into two groups using lottery method of 20 each. Twenty patients underwent primary closure of the wound while other 20 underwent secondary closure. Post-operative pain, swelling and trismus were evaluated on third and seventh day of extraction.Results: The mean age of the patient was 31.57 years (ranging from 28 to 42). The mean VAS score for pain was more on third day in patients with primary closure (2.70±0.733). This finding was statistically significant (p